The role of hyaluronic acid in the design and functionalization of nanoparticles for the treatment of colorectal cancer - de Paula, Mariana Carlomagno [UNESP]; Carvalho, Suzana Gonçalves [UNESP]; Silvestre, Amanda Letícia Polli [UNESP]; dos Santos, Aline Martins [UNESP]; Meneguin, Andréia Bagliotti [UNESP]; Chorilli, Marlus [UNESP] (Elsevier, 2023)
Despite advances in new approaches for colorectal cancer (CRC) therapy, intravenous chemotherapy remains one of the main treatment options; however, it has limitations associated with off-target toxicity, tumor cell resistance due to molecular complexity and CRC heterogeneity, which lead to tumor recurrence and metastasis. In oncology, nanoparticle-based strategies have been designed to avoid systemic toxicity and increase drug accumulation at tumor sites. Hyaluronic acid (HA) has obtained significant attention thanks to its ability to target nanoparticles (NPs) to CRC cells through binding to cluster-determinant-44 (CD44) and hyaluronan-mediated motility (RHAMM) receptors, along with its efficient biological properties of mucoadhesion. This review proposes to discuss the state of the art in HA-based nanoparticulate systems intended for localized treatment of CRC, highlighting the importance of the mucoadhesion and active targeting provided by this polymer. In addition, an overview of CRC will be provided, emphasizing the importance of CD44 and RHAMM receptors in this type of cancer and the current challenges related to this disease, and important concepts about the physicochemical and biological properties of HA will also be addressed. Finally, this review aims to contribute to the advancement of accuracy treatment of CRC by the design of new platforms based on by HA.
Keywords: CD44; Colorectal Cancer; Hyaluronic acid; Nanoparticles; RHAMM receptors